S0502: A SWOG Phase III Randomized Study of Imatinib, With or Without Bevacizumab, in Patients With Untreated Metastatic or Unresectable Gastrointestinal Stromal Tumors. (17th November 2015) - Blanke, Charles D.; Rankin, Cathy; Corless, Christopher; Eary, Janet F.; Mulder, Karen; Okuno, Scott H.; George, Suzanne; Heinrich, Michael
Abstract : Lessons Learned: Despite having significant rationale, S0502 failed to accrue for a number of reasons. Vetting a trial first, with scientific experts and funding agencies, does not guarantee success, especially when dealing with a rare tumor and/or one with an existing highly effective therapy. In the present case, adding an intravenous drug to an oral medication as part of a regimen expected to be continued for many years likely decreased patient (and physician) convenience and, thus, interest in the study. Background: Imatinib mesylate, a potent inhibitor of the KIT and PDGFR tyrosine kinases, is highly effective in the treatment of advanced gastrointestinal stromal tumors (GISTs). However, most imatinib‐treated tumors eventually become resistant, accounting for a median progression‐free survival of 19–23 months. Expression of vascular endothelial growth factor (VEGF) correlates with poor prognosis in GIST; bevacizumab, a monoclonal antibody against VEGF, is effective in a variety of solid tumors. We postulated combination therapy with imatinib plus bevacizumab would benefit patients with advanced GIST, particularly those reliant on VEGFA‐dependent angiogenesis. Methods: Patients with metastatic or surgically unresectable GIST were eligible for this phase III open‐label clinical trial, S0502. At registration, patients were randomly assigned to either imatinib 400 mg (standard) or 800 mg (patients with exon 9 KIT mutations), or imatinib plus bevacizumab, 7.5 mg/kg i.v. every 3 weeks. Patients were treated to progression, symptomatic deterioration, unacceptable toxicity, treatment delay greater than 4 weeks, or patient choice to withdraw from the study. The primary objective was to determine whether the addition of bevacizumab to imatinib would improve progression‐free survival (PFS) in first‐line treatment of incurable GIST. Results: S0502 opened on April 15, 2008. As of fall 2009, only 12 patients from at least 178 eligible SWOG centers plus those participating through Cancer Trials Support Unit had been entered in the study. Despite an aggressive promotion scheme involving the other cooperative groups and a major GIST patient advocacy group, accrual remained slow. The trial was closed on October 1, 2009, having accrued only 2% of the 572 patients planned. No scientific conclusions were forthcoming because of the small number of patients entered in the study. Two patients of the 6 in the combination arm reported grade 3 toxicities, 1 with proteinuria and 1 with fatigue, upper gastrointestinal hemorrhage, and anemia. Conclusion: No conclusions may be drawn from this trial and, thus, the combination of imatinib plus bevacizumab cannot be recommended for use. Abstract : 经验 尽管S0502研究有明确的理论基础, 但由于种种原因未能完成患者招募。 首先从科学专家角度和资助机构角度来审查一项研究并不能确保研究的成功, 尤其是当研究对象为罕见肿瘤和(或)已有非常有效的疗法时。 本研究在预期会持续多年的治疗方案中口服用药基础上添加了一种静脉药物, 很可能减少患者(和医生)的便利性, 因此影响了这项研究。 摘要 背景 . 甲磺酸伊马替尼是KIT和PDGFR酪氨酸激酶的强抑制剂, 治疗晚期胃肠道间质瘤(GIST)非常有效。但是多数经伊马替尼治疗的患者最终会产生耐药, 中位无进展生存为19 ∼ 23个月。血管内皮生长因子(VEGF)的表达与GIST预后不佳有关, 而抗VEGF单克隆抗体贝伐珠单抗在多种实体瘤中显示出有效性。我们假设晚期GIST患者(尤其是与VEGFA依赖性血管生成相关者)能够从伊马替尼与贝伐珠单抗的联合治疗中获益。 方法 . 本项开放标签III期临床试验(S0502)纳入了转移性或不可手术切除的GIST患者。患者在注册时随机分配至伊马替尼400 mg(标准患者)或800 mg(外显子9 KIT 突变患者), 或者伊马替尼联合贝伐珠单抗(7.5 mg/kg静脉注射, 每3周一次)治疗。治疗持续至患者发生疾病进展、症状恶化、不可接受的毒性事件、治疗推迟大于4周或患者选择退出研究为止。主要目的为确定伊马替尼基础上联合贝伐珠单抗用于一线治疗不能治愈的GIST患者能否改善无进展生存(PFS)。 结果 . S0502研究于2008年4月15日启动。至2009年秋天, 从至少178家符合标准的SWOG中心及通过癌症临床试验支持单位参加的中心中, 仅入组12例患者。尽管积极宣传计划还涉及了其他协作组和一个重要的GIST患者宣传小组, 招募入组仍然十分缓慢。本项临床试验于2009年10月1日关闭时仅入组了计划中572例患者的2%。由于研究入组患者数过少, 我们无法得出科学性的结论。联合组2/6例患者报告了3级毒性事件, 1例为蛋白尿, 另1例为疲乏、上消化道出血和贫血。 结论 . 本项临床试验无法得出结论, 因此不能对伊马替尼联合贝伐珠单抗的方案提出建议。 The Oncologist 2015;20:1353–1354